2009
DOI: 10.1088/1475-7516/2009/12/017
|View full text |Cite
|
Sign up to set email alerts
|

How the cosmological constant affects gravastar formation

Abstract: Here we generalized a previous model of gravastar consisted of an internal de Sitter spacetime, a dynamical infinitely thin shell with an equation of state, but now we consider an external de Sitter-Schwarzschild spacetime. We have shown explicitly that the final output can be a black hole, a "bounded excursion" stable gravastar, a stable gravastar, or a de Sitter spacetime, depending on the total mass of the system, the cosmological constants, the equation of state of the thin shell and the initial position o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…Note also that if L e = L i , the mass of the shell is zero and no object is formed. Recently we have shown that in order to have a physically acceptable stable shell between two spacetimes with cosmological constants, the inner cosmological constant must be greater than that outer one (Chan et al 2009b), which is in agreement to the gravastar requirement proposed by Horvat and Ilijic (2007). Our present work is completely coherent with this previous result since here it is not possible to have a stable thin shell.…”
Section: The Analysis Of the Potentialsupporting
confidence: 91%
See 4 more Smart Citations
“…Note also that if L e = L i , the mass of the shell is zero and no object is formed. Recently we have shown that in order to have a physically acceptable stable shell between two spacetimes with cosmological constants, the inner cosmological constant must be greater than that outer one (Chan et al 2009b), which is in agreement to the gravastar requirement proposed by Horvat and Ilijic (2007). Our present work is completely coherent with this previous result since here it is not possible to have a stable thin shell.…”
Section: The Analysis Of the Potentialsupporting
confidence: 91%
“…Instead of it reduces itself to a point-like object. This can be seen directly from the analysis of the potential and confirmed by the relation between the cosmological constants (L i > L e ), which is imposed in order to have a positive shell mass, and which violates the condition which had been already proposed by two of us, in another paper (Chan et al 2009b), that is, L i < L e to have stable structures. It is remarkable that if i = e there is no shell (its mass is zero), although it is not true if m = 0 .…”
Section: Final Remarkssupporting
confidence: 58%
See 3 more Smart Citations